2016
DOI: 10.5943/cream/6/4/5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions for secondary mycelial growth of wild macrofungi from selected areas in Central Luzon, Philippines

Abstract: This work highlighted the optimum culture conditions for secondary mycelia of selected Philippine wild macrofungi. The growth of different macrofungal species were evaluated on various indigenous culture media namely: coconut water gulaman, corn grit decoction gulaman, rice bran decoction gulaman, potato sucrose gulaman and potato dextrose agar (control). The effect of different physical conditions such as pH, illumination and temperature was also investigated. The daily mycelia diameter, mycelial density and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
3
17
1
Order By: Relevance
“…This suggested that this mushroom can grow in a wide range of pH. In general, mushrooms can grow in a wide range of pH of the medium [30]. Interestingly, Jayasinghe et al [35] confirmed it on his report that G. lucidum strains could grow on potato dextrose agar at a broad pH range, such as pH 5.0-9.0.…”
Section: Influence Of Culture Mediamentioning
confidence: 84%
See 2 more Smart Citations
“…This suggested that this mushroom can grow in a wide range of pH. In general, mushrooms can grow in a wide range of pH of the medium [30]. Interestingly, Jayasinghe et al [35] confirmed it on his report that G. lucidum strains could grow on potato dextrose agar at a broad pH range, such as pH 5.0-9.0.…”
Section: Influence Of Culture Mediamentioning
confidence: 84%
“…Furthermore, Sung et al [44] observed no obvious difference in the colony diameter of Ophiocordyceps longissima between light and dark conditions on solid media. In contrary, Kalaw et al [30] revealed that illumination significantly influenced the mycelial growth of five mushroom species on solid medium: L. sajor-caju and S. commune (CLSU strain), whereas dark condition showed maximum growth of G. lucidum (strain B), L. tigrinus (CLSU strain), G. lucidum (strain A), and C. cinerea (Sto. Domingo strain).…”
Section: Influence Of Physical Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…It can be seen that the three strains could grow from pH of 5.5-8.0, but with optimum pH at 6.5-7.5 for La Clementina and Vinces and at 6.5-7.0 for Montalvo. Similarly, Rang-ayan and CLSU strains of V. volvacea showed favorable mycelial growth at a wide range of pH with very thick mycelia at pH 7.5-8.0 [8]. In liquid culture, the optimum pH of V. volvacea was at pH 6.0 [9].…”
Section: Effect Of Culture Media and Phmentioning
confidence: 92%
“…This finding conforms with the study of Dulay et al [9] who reported that Sabouraud dextrose broth produced the highest biomass yield of Schizophyllum commune, Ganoderma lucidum, V. volvacea, and Pleurotus cystidiosus in submerged culture. However, in the evaluation of mycelial growth using indigenous culture media, the two strains of V. volvacea (Rang-ayan and CLSU) showed the maximum mycelial growth on potato sucrose gulaman (PSG) and corn grit gulaman (CGG) [8]. In addition, Ukoima et al [10] demonstrated that the highest growth of V. volvacea mycelia was observed on palm fiber culture medium.…”
Section: Effect Of Culture Media and Phmentioning
confidence: 99%